Question
Asked Oct 17, 2019

F(X) = -X4  + X+3

How to solve for x?

 

check_circleExpert Solution
Step 1

Given,

F(X) 3D — х4 + X2 + 3
help_outline

Image Transcriptionclose

F(X) 3D — х4 + X2 + 3

fullscreen
Step 2

To solve for X, equate F(X) = 0

F(X) 0
-X4X2+3 = 0
X4 -X2 3 = 0
Let a X2
а? — а — 3 %3D 0
Using quadratic formula, we get
-(1)t-1)2-4(1)(-3)
a
2(1)
1+ 13
2
help_outline

Image Transcriptionclose

F(X) 0 -X4X2+3 = 0 X4 -X2 3 = 0 Let a X2 а? — а — 3 %3D 0 Using quadratic formula, we get -(1)t-1)2-4(1)(-3) a 2(1) 1+ 13 2

fullscreen
Step 3

Now replacing a by X2,...

1+v13
X2
2
1+13
1+13
When X2
X +
2
=
2
1+13
1+13
X =
2
2
1-13
1-13
When X2
1-V13
1-13
X
2
2
help_outline

Image Transcriptionclose

1+v13 X2 2 1+13 1+13 When X2 X + 2 = 2 1+13 1+13 X = 2 2 1-13 1-13 When X2 1-V13 1-13 X 2 2

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour*

See Solution
*Response times may vary by subject and question
Tagged in

Math

Algebra

Polynomials